Delayed presentation of cerebral schistosomiasis presenting as a tumor-like brain lesion. Issue 4 (August 2018) - Suthiphosuwan, Suradech; Lin, Amy; Gao, Andrew F; Munoz, David G; Spears, Julian; Bharatha, Aditya
Schistosomiasis is the second most common parasitic infection worldwide. North America is a nonendemic area. However, there are occasional case reports among travelers and immigrants from endemic regions. We describe a case of a 55-year-old Canadian woman who presented with first episode of seizure. Her magnetic resonance imaging scan revealed a mass-like lesion involving the left anterior temporal lobe. The lesion showed T1 hypo- and T2 hyperintense with perilesional brain edema. On post-gadolinium-enhanced T1-weighted sequence, the lesion showed multiple small nodular and linear enhancements, also called an "arborized" appearance. Initially, the lesion was thought to be a malignant tumor. She underwent left anterior temporal lobe resection. Histologic examination showed parasitic eggs with a characteristic lateral spine consistent with Schistosoma mansoni infection. Upon subsequent questioning, it was revealed that the patient lived in Ghana from the ages of 8–10 years and she visited Ghana again 10 years prior for two weeks. She recalled swimming in beaches and rivers. Latent disease, as in this case with presentation, many years or decades after presumed exposure is rare but has been reported. Characteristic magnetic resonance imaging findings may suggest the diagnosis and facilitate noninvasive work-up.